10 days that unexpectedly changed America - Werbe, Susan; Berlinger, Joe.; Cutler, R. J.; Davis, Kate, 1960 February 23-; Epstein, Michael; Epstein, Robert P., 1955-; Friedman, Jeffrey, 1951-; Goodman, Barak; Heilbroner, David; Kennedy, Rory.; Maggio, John.; Moll, James; et al. ([Burlington, VT] : A & E Home Video ; New York : Distributed by New Video, 2006)
Massacre at Mystic: The first time the English settlers engaged in the slaughter of Native Americans after years of relatively peaceful coexistence. Shays' Rebellion: A violent protest against dept collection and taxation motivated George Washington to come out of retirement to help strengthen the fragile new nation which led to the Constitution and the Bill of Rights. Gold rush: The discovery of gold spurred tremendous financial and physical growth throughout the West. Antietam: On September 17, 1862, there were 23,000 casualties on both sides of this Civil War battle, making this the bloodiest day in American History. The Union victory enabled President Lincoln to issue the Emancipation Proclamation, making foreign support of the Confederacy all but impossible. The homestead strike: Harsh working conditions at Carnegie's Homestead steel mill led to a union strike. Murder at the fair: Set against the backdrop of the 1901 World's Fair, the assassination of President William McKinley ushered in a new Progressive Era under the presidency of Theodore Roosevelt. Scopes: The courtroom battle between William Jennings Bryan and Clarence Darrow over the teaching of evolution in a small Tennessee town underscored a deep schism within the American psyche. Einstein's letter: Albert Einstein's letter to FDR urged the development of an unthinkably powerful new weapon. When America was rocked: Elvis Presley's appearance on The Ed Sullivan show on September 9, 1956, signified a whole new culture that involved teenage independence, sexuality, race relations and a new form of music. Freedom summer: In 1864, three Civil Rights workers were murdered by the Ku Klux Klan in Mississippi.
Disc 3. Einstein's letter : July 16, 1939 / written by John Maggio ; produced & directed by John Maggio and Barak Goodman ; produced by Ark Media -- When America was rocked : September 9, 1956 / produced by Sidney Beaumont ; directed by Bruce Sinofsky -- Freedom summer : June 21, 1964 / produced & directed by Marco Williams ; produced by Two Tone Productions.
DVD; region 1, NTSC; Dolby Digital stereo.
Narrators, Hector Elizondo, Zachary Drake, Jeffrey Wright, Martin Sheen, Terry Kinney, John Scherlis, Campbell Scott, Joe Morton.
Directors of photography, Harris Done, Ramin Fathie, Michael Chin, Tom Hurwitz, Michael Neumann, Bob Richman, Stephen McCarthy ; editors, Michael Mayhew, Arash Avrom, Bill Weber, R.A. Fedde, Adam Zucker, Kristine Smith, Kate Davis, David Heilbroner, Nancy Kennedy, Sakae Ishikawa, Kris Liem ; music, Nathan Wang, Michael Montes, Sheldon Hirowitz, Wendy Blackstone, Joel Harrison, Gary Lionelli, J.J. Appleton, Tom Bresh, Christopher Tin.
Special features: Disc 4. "History in the making" featurette.
Keywords: United States -- History; Pequot War, 1636-1638.; Shays' Rebellion, 1786-1787.; Gold mines and mining -- History; Antietam, Battle of, Md., 1862.; Homestead Strike, Homestead, Pa., 1892.; McKinley, William, -- 1843-1901 -- Assassination; Scopes, John Thomas -- Trials, litigation, etc; Einstein, Albert, -- 1879-1955.; Rock music -- History; Presley, Elvis, -- 1935-1977.; Civil rights workers -- History; Mississippi Freedom Project; United States -- History; Historical television programs; Documentary television programs; Documentary -- Television special; Historical -- Television special